Support and positioning of innovation dual technologies policy in defense industry in the strategy of Russian national branding - Danilova, Elena A. (Высокоэнергетические и специальные материалы: антитерроризм, безопасность и гражданское применение : сборник научных трудов XVII Международной конференции "HEMs-2022", 14-16 сентября 2022 г. (Республика Алтай, Россия))
The theses are devoted to the problem of positioning the policy of dual defense industry technologies in the strategy of national branding of the Russian Federation in the era of growing global challenges and threats. The innovative development of the defense industry is of decisive importance both directly for solving the problem of building up the defense and combat potential of the state, and from the point of view of the locomotive for the development of civil industries and the economy as a whole. Each subject of the defense industry, which has innovative potential, can act as an active actor in the strategy of national branding of the Russian Federation. In addition, the relevant response to the current geopolitical situation is the formation of blocks in the field of defense and security with alternative international partners. One of such blocks is BRICS, cooperation within which is possible both on military-economic (arms export, joint developments) and on the military-political line (joint military exercises and maneuvers) in the interests of approving the idea of a multipolar world.